Investigating the role of ascorbic acid and its transporters in medulloblastoma - Jones, Manon (2025)
Medulloblastoma is a highly malignant paediatric brain tumour, accounting for 20% of cases. Current treatment achieves a 70% 5-year-survival rate but can result in long-term neurological side effects. Treatment is further complicated by the disease’s heterogeneity, comprising four molecular subgroups: Group 3, Group 4, SHH and WNT. Novel therapeutic strategies are urgently needed to improve outcomes while addressing both treatment toxicity and the diverse molecular landscape. Adjuvant therapies that enhance treatment efficacy could reduce therapeutic doses and minimise side effects. A unique feature of the SHH subgroup is a collagen-rich extracellular matrix (ECM) shell, which is associated with improved survival, possibly by limiting tumour growth and invasiveness. This makes it a potential target for therapeutic manipulation in SHH tumours. Ascorbic acid (Vitamin C) plays a critical role as a co-factor in collagen production and could influence the collagen-rich ECM shell encapsulating SHH tumours. In addition, at high doses, ascorbic acid generates reactive oxygen species (ROS) via the Fenton reaction, leading to enhanced oxidative stress. Therefore, high-dose ascorbic acid could be a compelling candidate as an adjuvant treatment of SHH tumours, by promoting a tumour-restrictive microenvironment and increasing oxidative stress to enhance current treatment efficacy.